(untitled) (Journal of Training and Development, 2016)
In my understanding, Rapid Market Appraisal (RMA) is a comprehensive study of an employment status in the specific occupational area at the particular local level. At the cross road of my job career, I came to know that the development of this process grew out of a frustration with lengthy, costly and intensive formal market survey. I argue that this process provides a quick, flexible and effective way of collecting, processing, and analyzing information and data about labour markets. It explores information about the vocational-technical training institutions working effectively in the respective field. It also supplies detailed information like occupational opportunities, training needs, individual needs, and future prospective in the work of world at local level. Based on my practical experiences, I claim it as one of the effective tools for assessing the training needs for training design for the under-developing countries.